UJI EFEK ANALGETIK EKSTRAK ETANOL 96% DAUN KELAPA SAWIT (Elaeis guineensis Jacq) TERHADAP MENCIT (Mus Musculus) YANG DI INDUKSI ASAM ASETAT - Rakhil Zulfansyah; Nur Mahdi; Raisha Hamiddani S (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2023)
In Indonesia, especially in Kalimantan, many oil palm plants (Elaeis guineensis Jacq) are found. The potential of this plant has not been fully exploited. A number of tests have been carried out, namely as an antioxidant, burn wound, larvicide and antibacterial. This research was conducted to identify the analgesic effectiveness of oil palm leaf extract (Elaeis guineensis Jacq) on white mice (mus musculus) given acetic acid. The extraction method used is meseration. The analgesic test uses a chemical stimulation method. 25 mice were divided into 5 groups (negative group Na CMC 0.5%, positive group Paracetamol, dose I 100 mg/kgBW, dose II 300 mg/kgBW, dose III 500 mg/kgBW). Each group was treated orally, after 30 minutes they were given 1% acetic acid intraperitoneally, then the total number of wriths, percent protection and one way ANOVA test were calculated. The experimental results showed that the positive control percent protection was 57.44%, dose I was 34.78%, dose II was 52.10%, and dose III was 70.87%. The results of the one way ANOVA test analysis showed significant differences between each treatment group except for dose II 300 mg/kgBB. It can be concluded that the ethanol extract of oil palm leaves (Elaeis guineensis Jacq) has effectiveness as an analgesic and at dose II 300 mg/kgBW is the most effective dose because it is close to the percent protection of the positive control (Paracetamol).